ANALISIS KEPUASAN NASABAH BPR DILIHAT DARI KUALITAS PELAYANAN - Indri yenni (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2016)
Customer is the king who needs to be respected and well served. The study lookedat the problem of service for customer satisfaction that comes deal to BPR SL 50 Kota toobtain financial services they need.This study used a qualitative approach, a descriptive analysis of the data, wherethe interpretation of existing data and information using the model of interpretation. Thisstudy are five factors in terms of customer service: friendliness, service information, easeof service, cleanliness and comfort of the environment and the price of services. Thedominant factor to the increase in customer satisfaction factor is the ease of service andtariffs.